A systematic review of the factors that would affect the distribution of green hydrogen in Valle del Cauca - Díaz-Gómez, Jenny Fernanda (2024)
Hydrogen has become an object of study as a fuel to generate energy through renewable sources such as biomass, playing an important element in the transition towards a low-carbon economy. In this way, challenges arise for applying this fuel, such as the logistical elements to consider in the projects sought to be implemented. The present study proposal focuses on analyzing distribution factors of green hydrogen applied specifically to sugarcane bagasse generated in Valle del Cauca, analyzing between storage methods such as compressed or liquid hydrogen and transportation through alternatives such as compressed gas pipes or tanks.